PROTECTION BUSINESS SERVICES IN BUSINESS RENTAL CARS (Studies in Baturaja) - Titie Syahnaz Natalia (KOLEGIAL, 2020)
This study aims to determine how the legal protection for businesses in car rental services in the city of Baturaja. This study uses empirical-normative research. That the legal protection for businesses in car rental services in the city of Baturaja refers to the provisions of Law No. 8 of 1999 on Consumer Protection and the substance of the car rental agreement. Settlement of disputes over damages arising from the negligence of the consumer refers to the substance of the agreement is the settlement of the problem solved by means of non-litigation, namely through deliberation to reach consensus, and compensation on the part of consumers to businesses.